The research: beyond the ranking of the universities: La investigación: mas allá del ranking de las universidades - De La Cruz Vargas, Jhony Alberto (2019)
One of the most important processes and of which all other university activities are sustained is research. Research is creation, original production, development of argumentation and coherence of ideas, exhaustive review-deep reflection, solving mysteries and, ultimately, giving focus to dreams. The integral conceptual approach, proposed by Rico1, for whom the research "is to colonize a small or large plot, to plant, cultivate, harvest and distribute its fruits, so that later others come to improve, optimize and overcome our task".   DOI:  10.25176/RFMH.v19.n1.1786